1995
DOI: 10.2337/diacare.18.1.64
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Topical Basic Fibroblast Growth Factor on the Healing of Chronic Diabetic Neuropathic Ulcer of the foot: A pilot, randomized, double-blind, placebo-controlled study

Abstract: Topical application of bFGF has no advantage over placebo for healing chronic neuropathic diabetic ulcer of the foot. Because diabetes causes significant wound-healing defects, we hypothesized that using a single growth factor might be insufficient to accelerate wound closure of diabetic ulcers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
158
0
4

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(165 citation statements)
references
References 18 publications
3
158
0
4
Order By: Relevance
“…The reported diabetic ulcer healing rates ranged from 33 to 57.5% at a cutoff time of 12-20 weeks, when the growth factors PDGF or FGF were used in controlled trials (17,18). In a small pilot randomized double-blind study reported by Richard et al (18), nine chronic neuropathic plantar foot ulcers (Wegner grade I-III) were treated with topical FGF for a total of 18 weeks.…”
Section: Hegf and Diabetic Foot Ulcersmentioning
confidence: 99%
“…The reported diabetic ulcer healing rates ranged from 33 to 57.5% at a cutoff time of 12-20 weeks, when the growth factors PDGF or FGF were used in controlled trials (17,18). In a small pilot randomized double-blind study reported by Richard et al (18), nine chronic neuropathic plantar foot ulcers (Wegner grade I-III) were treated with topical FGF for a total of 18 weeks.…”
Section: Hegf and Diabetic Foot Ulcersmentioning
confidence: 99%
“…Only a few well-controlled, randomized clinical trials have assessed the usefulness of growth factors in healing chronic ulcers, and the results have been largely discrepant. The use of recombinant PDGF was shown to improve diabetic ulcer healing, healing rates, and ulcer size, 101 and to improve healing rates in pressure ulcers, 102,103 but the use of recombinant FGF was not effective for diabetic ulcers, 104 nor was recombinant EGF effective for venous ulcers. 105 Although no side effects were attributed to the use of growth factors, none of the studies examined costs relative to those of more conservative therapy.…”
Section: Drug Therapymentioning
confidence: 99%
“…Investigation of skin transplants has shown that the survival rate of an implant after administration of bFGF rises, due to an increase in revascularization (Burges 1989). In animal models with diminished wound healing (mice with diabetes, with obesity, or in receipt of steroid treatment), bFGF increased the rate of wound healing (Richard et al 1995). Likewise, local application of bFGF in patients with diabetic ulcer led to an increase in healing rates (Albertson et al 1993, Okumura et al 1996.…”
mentioning
confidence: 99%
“…Clinical and animal experiments have shown that local application of growth factors may accelerate this restoration of vascularization/perfusion and lead to improvement of wound and fracture healing (Mustoe et al 1987, Sprugel et al 1987, Rifkin andMoscatelli 1989, Klingbeil et al 1991, Yasko et al 1992, Albertson et al 1993, Lind et al 1993, Kawaguchi et al 1994, Nash et al 1994, Nielsen et al 1994, Steenfos et al 1994, Heckman et al 1995, Nagai et al 1995, Richard et al 1995, Okumura et al 1996, Wang and Aspenberg 1996, Beer et al 1997, Davidson et al 1997, Leunig et al 1997, Bostrom and Camacho 1998, Kato et al 1998, McGee et al 1998, Wieman et al 1998, Corral et al 1999, Radomsky et al 1999, Bouxein et al 2001, Govender et al 2002, Luppen et al 2002, Einhorn et al 2003, Hom and Manivel 2003.…”
mentioning
confidence: 99%